Cigarette smoking: knowledge and attitudes among Mexican physicians - TAPIA-CONYER ROBERTO; CRAVIOTO PATRICIA; ROSA BLANCA DE LA; GALVÁN FERNANDO; GARCÍA-DE LA TORRE GUADALUPE; KURI PABLO (Instituto Nacional de Salud Pública, 1997)
Objective. To determine the prevalence of the smoking habit among Mexican physicians as well as some of their attitudes and information on specific issues concerning smoking. Material and methods. In 1993, a survey was carried out among 3 568 physicians of the three major official health care institutions in Mexico City. A questionnaire designed for The Mexican National Survey of Addictions (ENA 1993) was used. Prevalence of cigarette smoking, age of onset, number of cigarettes per day; also information and attitudes concerning smoking were assessed. Results. The mean age was 37, 66% were males. Of the 3,488 (98%) surveyed, 26.9% were smokers (62% daily), 20.6% were ex-smokers and 52.5% non-smokers. There were differences related to age and sex (p< 0.05). Of daily smokers, 36% smoked between 1 and 5 cigarettes. There was a significant trend among ex-smokers that linked the time they had ceased smoking with the fear to start smoking again. Physicians were well informed of the relationship between cigarette smoking and lung cancer. Over 80% considered tobacco an addictive drug but only 65% were in favor of banning smoking from their workplaces and over 10% were not aware that it is forbidden to smoke inside health care facilities. Conclusions. These results differ from other studies that find the prevalence of smoking among physicians lower than in the general population. Our study revealed a greater prevalence of the smoking habit among female physicians and the number of cigarettes smoked per day was greater than in the general population regardless of sex.